AB0778 Long-Term Intervention with Weight Loss in Patients with Concomitant Obesity and Knee Osteoarthritis: A Randomised Trial (The Light Study). (10th June 2014) - Bliddal, H.; Christensen, P.; Bartels, E.M.; Leeds, A.R.; Astrup, A.; Christensen, R.
Abstract : Background: Formula low-energy diet reduces weight effectively in obese patients with knee osteoarthritis (KOA) but how to achieve weight maintenance is not clear. Objectives: To compare two different dietary interventions helping KOA patients maintain a lower body weight and prevent a total knee alloplasty (TKA) after three years as a sequel to the previous CAROT lifestyle intervention trial. Methods: Patients completing the CAROT study (NCT00655941 ) were considered eligible for inclusion in the LIGHT study, and invited to participate (ClinicalTrials.gov Identifier: NCT00938808 ). One-hundred-and-fifty-three participants (BMI 33.3 [SD4.6] kg/m 2 ; mean age 63.8 [SD 6.3] years, 83% women) were randomised to one of two interventions using formula low-energy-diet products with different strategies for weight maintenance. The interventions were either three intensive periods of 5 weeks/year of a low-energy formula diet of 3400kJ/day [IS group] or an offer to use 1-2 formula products as meal replacements daily [MR group]. Attention by dieticians and amount of freely provided formula products (Cambridge Weight Plan®) were similar in both groups throughout the 3 year period. The ITT population (153 patients) was included in the analyses independent of reasons for withdrawal using non-responder imputation. We used ANCOVA for continuous data, and chi-square statistics for dichotomous outcomes. When recruited at baseline, the average weight loss was 11.3 kg and mean Kellgren-Lawrence score of the worst joint compartment was 3.6±0.9 (SD) and 3.3±0.8 (SD) in the IS and MR groups respectively. Results: Retention was similar in both groups (IR: 69.7% vs. MR: 71.4%): 108 participants completed the study. Maintenance of body weight after three years, group x time, was better in the IS group than in the MR group (p=0.0001, Figure 1). TKA surgery rates were not different either (IS: 8/76; MR: 12/77; P=0.35). Conclusions: It is possible to maintain weight loss throughout a 3-year period achieved using formula diet in an obese population with KOA by either of 2 formula diet strategies. Despite very bad knee at entry, relatively few of the participants chose a TKA during the study period. Acknowledgements: The study was supported by grants from the Oak Foundation, Velux Foundation; Cambridge Weight Plan, UK, the Danish Rheumatism Association, Augustinus Fonden, the A.P. Møller Foundation for the Advancement of Medical Science, Aase og Ejnar Danielsens fond, Bjarne Jensens Fond, and Hørslev Fonden Disclosure of Interest: H. Bliddal Grant/research support: The Cambridge Weight Plan, P. Christensen Grant/research support: the Cambridge Weight Plan, E. Bartels: None declared, A. Leeds Employee of: the Cambridge Weight Plan, A. Astrup: None declared, R. Christensen Grant/research support: The Cambridge Weight Plan DOI: 10.1136/annrheumdis-2014-eular.5634